ANN Controlled VSC with Harmonic Reduction for VAR Control of Transmission Line - Ram Shankarrao Dhekekar; N V Srikanth (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
Complete close-loop smooth control of reactive power can be achieved using shunt connected FACTS devices. STATCOM is one of the shunt connected FACTS device which can be utilized for the purpose of reactive power compensation. Intelligent FACTS devices make them adaptable and hence it is emerging in the present state of art. This paper presents close loop control techniques based on artificial neural networks (ANNs) to control reactive power generated by long transmission line over wide range so as to maintain constant voltage profile at the receiving end. With ANN technique and H-bridge multilevel VSC topology harmonics are eliminated to accepted level. A 9-Level H-Bridge VSC based STATCOM is used to handle the reactive power of the line .The close loop control is achieved by PI and neural network. . This paper is about real time simulation and implementation of PI controlled VSC STATCOM for 750km lab model of artificial transmission line. PI controller and neural network control schemes implemented and investigated. With Matlab simulation and actual testing proves that these devices when installed, they keep the bus voltage same as reference voltage (sending-end voltage). The results are prominent and give a way for real-time implementation of the proposed control schemes. These control schemes are simulated for the real-time control along with real-time modeling and simulations. Relative Harmonic analysis, for both the schemes are discussed. The results are prominent and give a way for real-time implementation.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.206